Hubungan Panjang Berat Ikan Biji Nangka (Upeneus Moluccensis) di Pelabuhan Perikanan Samudera, Belawan - Cristhyn Agustina Damanik; Mardame Pangihutan Sinaga (Fakultas Pertanian Universitas Samudra, 2025)
This study was conducted with the aim of measuring the length and weight of the Jackfruit Seed Fish (Upeneus moluccensis). The number of fish samples used was 111 fish. With the overall length of the fish samples ranging from 105 mm to 165 mm, where the dominant total length of the fish caught was in the average range of 130.31 mm. Meanwhile, the weight of the Jackfruit Seed Fish (Upeneus moluccensis) ranged from 18 to 66 grams, with an average fish weight of 35.76 grams. The results of the calculation of the b value obtained for the Jackfruit Seed Fish (Upeneus moluccensis) at the Belawan Ocean Fishery Port were 2.86. Based on the b value obtained, it can be stated that the length of the fish weight is <3, (negative allometric) which means that the growth in length is faster than the growth in weight.